Impact of adherence to treatment with fluticasone propionate/salmeterol in asthma patients. (July 2014) - Ismaila, A.; Corriveau, D.; Vaillancourt, J.; Parsons, D.; Stanford, R.; Su, Z.; Sampalis, J. S.
Abstract Objective: Low adherence with asthma treatment may be associated with suboptimal outcomes and hence create a treatment gap in the real-life setting. The objective of this study was to assess the long-term association between adherence to treatment with fixed-dose fluticasone propionate/salmeterol (FSC) and the risk of exacerbations and health care utilization in patients with asthma. Research design and methods: Observational single cohort study utilizing the Quebec Health Insurance databases. All patients (age >12 years) with a diagnosis of asthma (ICD9-CM 493.xx) between 2001 and 2010 were entered into the study cohort at the time of their first prescription for FSC at any dose. Follow-up continued to the last known claim or death. Adherence to treatment was ascertained as compliance (medication possession ratio ≥80%) and persistence (absence of treatment gap ≥30 days). Main outcome measures: Outcomes assessed were exacerbations defined as one of the following: use of oral corticosteroid (OCS), emergency room (ER) visit for asthma or hospitalization for asthma. Asthma related health care resource utilizations ascertained were number of prescription claims for rescue medications, ER visits, hospitalizations, intensive care unit (ICU) stay, intubations, and general practitioner (GP) and respirologist visits. Results: A total of 19, 126 patients were included in the study. The proportion of compliant and persistent patients were 42.7% and 29.3% respectively. Multivariate logistic regression analyses showed a significantly reduced adjusted odds of exacerbations for compliant (OR = 0.48; 95% CI: 0.44–0.54) and persistent patients (OR = 0.42; 95% CI: 0.38–0.48). Similarly, significantly lower rates of health care utilization were observed for compliant and persistent patients. Conclusions: The results of this large population-based study have shown that increased adherence to treatment with FSC is associated with lower risk for exacerbations, lower rescue medication use and lower health care utilization in asthma patients. Despite the typical limitations of an administrative database study including validity of the diagnosis, the fact that compliance and persistence are calculated based on filled claims which does not guarantee that the patients actually took their medications, and the absence of clinical and laboratory data, the findings have implications for physician and patient awareness of the importance of adherence in the management of asthma.